EKSISTENSI PERILAKU PELAKU USAHA DI PASAR KAWASAN WISATA RELIGI MAKAM GUS DUR PERSPEKTIF PASAL 1 ANGKA 3 UNDANG-UNDANG PERLINDUNGAN KONSUMEN NOMOR 8 TAHUN 1999 DAN ETIKA BISNIS ISLAM - Muzizah, Anti Anfaul Lisani (Program Studi Hukum Ekonomi Syariah, Universitas Hasyim Asy'ari, 2023)
Abstrak: This study intends to analyze the existence of the behavior of business actors in the religious tourism area of Gus Dur's tomb, to analyze the review of article 1 number 3 of the consumer protection law number 8 of 1999 against behavior business actors in the Gus Dur tomb tourism area, analyzing the review of Islamic business ethics on the behavior of business actors in the Gus Dur tomb religious tourism area There are two sources of data in this study, namely primary data sources and secondary data. Sclesu collects data, to analyze the author using deductive and descriptive methods. Analysis of the data obtained from this study aims to identify and describe the views of Article 1 number 3 number 8 of 1999 of the law on legal protection and Islamic business ethics on the behavior of business actors in the market area of Gus Daksiour's tomb so that business actors can carry out trading practices in accordance with Article 1 point 3 UUPK no. 8 of 1999 and Islamic business ethics